Transmitting silks of maize have a complex and dynamic microbiome - Eman M. Khalaf (Nature Portfolio, 2021)
Abstract In corn/maize, silks emerging from cobs capture pollen, and transmit resident sperm nuclei to eggs. There are > 20 million silks per U.S. maize acre. Fungal pathogens invade developing grain using silk channels, including Fusarium graminearum (Fg, temperate environments) and devastating carcinogen-producers (Africa/tropics). Fg contaminates cereal grains with mycotoxins, in particular Deoxynivalenol (DON), known for adverse health effects on humans and livestock. Fitness selection should promote defensive/healthy silks. Here, we report that maize silks, known as styles in other plants, possess complex and dynamic microbiomes at the critical pollen-fungal transmission interval (henceforth: transmitting style microbiome, TSM). Diverse maize genotypes were field-grown in two trial years. MiSeq 16S rRNA gene sequencing of 328 open-pollinated silk samples (healthy/Fg-infected) revealed that the TSM contains > 5000 taxa spanning the prokaryotic tree of life (47 phyla/1300 genera), including nitrogen-fixers. The TSM of silk tip tissue displayed seasonal responsiveness, but possessed a reproducible core of 7–11 MiSeq-amplicon sequence variants (ASVs) dominated by a single Pantoea MiSeq-taxon (15–26% of sequence-counts). Fg-infection collapsed TSM diversity and disturbed predicted metabolic functionality, but doubled overall microbiome size/counts, primarily by elevating 7–25 MiSeq-ASVs, suggestive of a selective microbiome response against infection. This study establishes the maize silk as a model for fundamental/applied research of plant reproductive microbiomes.